Problematic aspects in the field of guaranteeing the observance of human rights and freedoms in the activities of the National Police of Ukraine while ensuring public safety - Palii, Valerii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
Problematic aspects in the field of guaranteeing the observance of human rights and freedoms in the activities of the National Police of Ukraine while ensuring public safety have been analyzed. Two groups of problems faced by law enforcement officers are outlined – general and specific. It is proposed to develop and introduce into the curricula a special course «Concepts and reasons for the use of restrictive measures by law enforcement officers» at higher educational institutions with specific training conditions that train police officers. The conclusions indicate that during the exercise of their powers and the performance of assigned tasks in the field of ensuring public order and public safety, the employees of the units of the NPU are faced with separate problems, which can be divided into two groups – general and specific. In order to eliminate them, it is necessary to pay attention, first of all, to the constant study and verification of knowledge by the personnel of international standards of compliance with the rights and freedoms of man and citizen, the norms of the Constitution of Ukraine, current legislation, their professional duties, as well as to focus efforts on acquiring skills in their application to practice. To do this, it is necessary to develop and introduce into the curricula a special course «Concepts and reasons for the use of restrictive measures by law enforcement officers» in higher educational institutions with specific training conditions that train police officers, as well as separately emphasize this topic during the training of police officers in the system official training, while paying attention not only to theoretical knowledge, but also to the practice of its application – during tactical training, the application of practical skills of self-defense techniques, personal safety and physical impact, solving situational problems, considering positive and negative facts from the practical activities of law enforcement bodies, etc. It is also considered necessary to take measures for additional identification of the person who takes the tests using the information and telecommunication system «Information portal of the National Police of Ukraine».